Analysis of the Effect of Tax Knowledge Level and Service Quality on Taxpayer Compliance in KPP Pratama Semarang Gayamsari - Katrina Maita Dewi; Suwardi - Suwardi; Sugiyanta - Sugiyanta (Admisi dan Bisnis, 2022)
The purpose of this research is determine the effect of tax knowledge and service quality on taxpayer compliance in KPP Pratama Semarang Gayamsari. The population used in this study is the individual taxpayer employees who are registered at the Pratama Semarang Gayamsari Tax Service Office with a total of 15,901 people. This study is conducted against 100 respondents using the Non-Probability Sampling method with the Incidental sampling technique. Data analysis used is the instrumental test, classical assumption test, multiple linear regression analysis, and hypothesis testing. The results of this study indicate, that the level of tax knowledge and service quality has a positive and significant effect on taxpayer compliance. The results of the coefficient of determination show that the level of tax knowledge and service quality jointly contribute to taxpayer compliance by 32%. The remaining 68% of taxpayer compliance is influenced by other factors not examined in this study